From enfant terrible to eminence grise Donald Hutera discerns a change of gears for Bill T. Jones - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 1998)
PALABRAS CLAVE: Bill T. Jones, We Set Out Early...Visibility Was Poor.